Overview Equipment Safety Traditional Motor Boats at Tigaras Harbor Regency Simalungun North Sumatra Province - Driaskoro Budi Sidharta; Miran Miran; Reta Ayu Tarysha (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2022)
Ferry port Tigaras is in the district Simalungun Province Sumatra North is one harbour crossing on Lake Toba to to Island Samosir . Equipment safety passenger on traditional motorboat is things to do filled with all ships operating at the ferry port Tigaras at the moment To do cruise good from life jacket, lifebouy , rocket parachute, tools extinguisher fire and rope discharge 30 m. Study this aim for knowing a lot traditional motor boats that have not been complete equipment safety and quantity percentage tool safety met above traditional motorboat on the track Tigaras-simanindo.For Methodology research used is observation directly in the field , interviews , library / documentation. Analysis used is analysis in the form of Gap Analysis as comparison Among existing state with secured situation. Based on Regulation Director General Communication Land Number : 3424/AP.402/DRJD/2020 About River And Lake Ships. Based on analysis the obtained conclusion that traditional motorboat on the track Tigaras-Simanindo not yet complete equipment safety in accordance with regulations governing and for Level of compliance tool safety on board traditional operating on the lake track Tigaras-Simanindo namely Life Jacket 35%, Life bouy 6%, Firefighter 0% fire , 100% for rope waste 30 m all boat already equips and 33% for Rocket Parachute.